2015
DOI: 10.1097/mco.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins and heat therapy for type 2 diabetes

Abstract: Heat therapy is a promising and inexpensive tool for the treatment of obesity and diabetes. We proposed that transient increments in nitric oxide and heat shock protein 70 levels may explain the benefits of heat therapy. We suggest that heat therapy (sauna: 80-100°C; hot tub: at 40°C) for 15 min, three times a week, for 3 months, is a safe method to test its efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 22 publications
1
53
0
Order By: Relevance
“…2,3 There are many factors involved in the development and treatment of insulin resistance, with the roles played by both thermal therapy and heat shock proteins (HSPs) receiving increased attention. [4][5][6][7] Furthermore, it has been suggested that HSPs may provide an early indicator of the onset of metabolic diseases, such as type 2 diabetes (T2DM), 8,9 while also acting as a possible biomarker for the chronicity of diabetes. 10 HSPs are synthesized in response to a number of physiological stressors, [11][12][13] and are individually characterized by their molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 There are many factors involved in the development and treatment of insulin resistance, with the roles played by both thermal therapy and heat shock proteins (HSPs) receiving increased attention. [4][5][6][7] Furthermore, it has been suggested that HSPs may provide an early indicator of the onset of metabolic diseases, such as type 2 diabetes (T2DM), 8,9 while also acting as a possible biomarker for the chronicity of diabetes. 10 HSPs are synthesized in response to a number of physiological stressors, [11][12][13] and are individually characterized by their molecular weight.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of iHSP70 is critical for the promotion of tissue repair, since the expression of this chaperone, by virtue of avoiding misfolded protein aggregates, confers cytoprotection and also exerts anti-inflammatory effects [39]. Hence, since aging is associated with chronic low-grade inflammation and impaired skeletal muscle repair, the activation of HSP70 expression and its effective response against cellular stress play a key role against cell dysfunction observed in aging.…”
Section: Anti-misfolding Protein Quality Control Systemsmentioning
confidence: 99%
“…In a recent study, our group observed that the ratio between plasma eHSP70 and cellular iHSP70 in lymphocytes from rats submitted to different loads of acute exercise (an acute stressful situation) can indicate the inflammatory status [34]. Indeed, extracellular to intracellular HSP70 ratio index (H-index) measured in peripheral blood mononuclear cells (PBMC) in relation to serum values has been recently assumed as novel and overall index of immunoinflammatory status of an individual [34,39,105,112]. The rationale for this is that the higher eHSP70 amounts, the more inflammatory signals are coming into play because eHSP70 is proinflammatory in nature.…”
Section: Anti-inflammatory Role Of Intracellular Hsp70mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, other markers of disease such as glycated haemoglobin (Krause et al . ), total cholesterol and LDL cholesterol (Gryka et al . ) have been shown to decrease with heat therapy.…”
mentioning
confidence: 99%